2012
DOI: 10.1038/ajh.2011.245
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor-Associated Hypertension and Its Organ Damage: Clinical Relevance for Resistant Hypertension

Abstract: The role of aldosterone in the pathogenesis of hypertension and cardiovascular diseases has been clearly shown in congestive heart failure and endocrine hypertension due to primary aldosteronism. In resistant hypertension, defined as a failure of concomitant use of three or more different classes of antihypertensive agents to control blood pressure (BP), add-on therapy with mineralocorticoid receptor (MR) antagonists is frequently effective, which we designate as "MR-associated hypertension". The MR-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 91 publications
2
65
0
1
Order By: Relevance
“…Multiple factors regulate sodium balance; in this study, we focused on mineralocorticoid receptor (MR). In recent studies, we identified novel coregulators of MR3, 4 and proposed a new pathological condition associated with aberrant MR activation, designated MR‐associated hypertension 5…”
mentioning
confidence: 99%
“…Multiple factors regulate sodium balance; in this study, we focused on mineralocorticoid receptor (MR). In recent studies, we identified novel coregulators of MR3, 4 and proposed a new pathological condition associated with aberrant MR activation, designated MR‐associated hypertension 5…”
mentioning
confidence: 99%
“…1 They can also suppress kidney damage in animal models of GN and diabetic nephropathy without affecting BP. [2][3][4][5][6] In addition, MR antagonists provide added protection against proteinuria and loss of renal function when used with standard antihypertensive therapies in patients with diabetic and nondiabetic CKD.…”
mentioning
confidence: 99%
“…21,22 The widespread locations of the MR are thought to explain the pleiotropic effects of aldosterone, including salt reabsorption, cardiac fibrosis, and vascular hypertrophy and inflammation resulting in reduced NO availability. Vascular inflammation leads to vascular fibrosis, whereas NO reduction leads to endothelial dysfunction and vasoconstriction.…”
Section: Volume Expansionmentioning
confidence: 99%
“…In the setting of CKD, the small GTPase protein Rac-1 also increases MR activation, causing hypertension. 22 Thus, MR-mediated hypertension is possible even in patients with normal aldosterone concentrations. Indeed, among 1688 nonhypertensive patients in the Framingham Heart Study, baseline plasma aldosterone levels predicted progression to hypertension, even among patients with normal aldosterone concentrations at baseline.…”
Section: Volume Expansionmentioning
confidence: 99%